LA NEUTRALIDAD VALORATIVA EN LA TEORÍA DEL DERECHO. LAS POSTURAS DE JOHN FINNIS Y JOSEPH RAZ - Ramírez Vargas, Luis Enrique (Revista de Derecho, 2020)
This paper addresses the methodological issue of value neutrality in the legal theory throught exposing the methodological positions of John Finnis and Joseph Raz. It is assumed that H.L.A. Hart’s theory of law constituted a paradigm shift in the legal philosophy of the last century thanks to the incorporation of elements of ordinary language philosophy which have resulted in a hermeneutic philosophy of law. The analysis will reveal the relationship between the degree of neutrality of each theory and the determination of its object studied, as well as the mutual conditioning between the two factors. Finally, I propose a solution to the objection raised by Julie Dickson to the finnisian methodology, which she considers to be committed to the thesis of the moral obligation of law.